Leisure activity and cognitive decline in incident Alzheimer disease. - Helzner, Elizabeth P; Scarmeas, Nikolaos; Cosentino, Stephanie; Portet, Florence; Stern, Yaakov (Arch Neurol, 2007)
BACKGROUND: High rates of leisure activity have been associated with reduced risk of Alzheimer disease (AD). OBJECTIVE: To determine whether prediagnosis leisure activity modifies the rate of cognitive decline in patients with AD. DESIGN: Inception cohort followed up longitudinally for a mean of 5.3 years (up to 13.9 years). SETTING: Urban community. PARTICIPANTS: A total of 283 patients with incident AD (mean age, 79 years; 56.2% Hispanic and 31.1% African American). MAIN OUTCOME MEASURES: Change in a composite cognitive score from diagnosis on and during the entire study follow-up. RESULTS: In multivariate-adjusted generalized estimating equation models of postdiagnosis change (n = 133), each leisure activity was associated with an additional yearly decline of 0.005 of a z-score unit in cognitive score (P = .17). In models expanded to include cognitive change during study follow-up, including evaluations before and after diagnosis (n = 283), each activity was associated with an additional yearly decline of 0.005 of a z-score unit in cognitive score (P = .03). The association was strongest for intellectual activities. CONCLUSIONS: Greater participation in prediagnosis leisure activities, especially intellectual activities, was associated with faster cognitive decline, supporting the hypothesis that the disease course in AD may vary as a function of cognitive reserve.
Keywords: Aged; Alzheimer Disease; Cognition; Cohort Studies; Disease Progression; Female; Follow-Up Studies; Humans; Leisure Activities; Male; Models, Neurological; Prognosis